Thermoelectric Conversion From Interface Thermophoresis and Piezoelectric Effects - Zeng, Yu-Jia; Liu, Yue-Yang; Pan, Hui; Ding, Zhong-Ke; Zhou, Wu-Xing; Tang, Li-Ming; Li, Baowen; Chen, Ke-Qiu (Frontiers in Physics, 2022)
Piezoelectric effect has proved itself to be a promising energy conversion mechanism that can convert mechanical energy into electricity. Here, we propose an indirect thermoelectric conversion mechanism based on a combination of the thermophoresis and piezoelectric effects. We first analyze this thermally driven mechanism using a simplified theoretical model and then numerically analyze a molecular dynamics (MD) simulation of a hybrid system constructed of a single-layer MoS2 nanoribbon and a concentric carbon nanotube. We show that the thermophoresis-induced piezoelectric output voltage can reach 3.5 V, and this value can be tuned using a temperature difference. The output voltage obtained using this mechanism is significantly higher than that obtained by heating piezoelectric materials directly. Given the generality of the thermophoresis effect in Van der Waals structures, this mechanism has potential applications in the conversion of thermal energy into electrical energy at the nanoscale level.